PENGARUH MOTIVASI, LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KINERJA PEGAWAI NON PNS UNIVERSITAS PENDIDIKAN GANESHA - Luh Wiwin Yuni Andarini; Komang Krisna Heryanda (Faculty of Economics and Business, Universitas Warmadewa, 2026)
Abstract This study aims to analyze the impact of motivation, work environment, and compensation on the performance of non-Civil Servant (PNS) employees at Ganesha University of Education. This research uses a quantitative approach with a survey method, involving 189 respondents. The data analysis results indicate that motivation has a positive impact on employee performance, while the work environment has a negative impact, and compensation has a positive impact on performance. The implications of these findings are important for the management of Ganesha University of Education to enhance the performance of non-PNS employees by paying attention to motivation, work environment, and fair compensation in line with employees' contributions.. Keywords: Motivation, Work environment, Compensation